The Effect Of hCG (Human Chorionic Gonadotropin) With Different Dosage ToOvulation And Eggs Quality Of Redfin Shark (Epalzeorhynchos frenatum) - Zulkifli Zulkifli; Netti Aryani; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe research was conducted from September to October 2018 in The Center for Research and Cultivivation of Ornamental Fish (BRBIH), Depok, West Java. The purpose of this research was to evaluate the effect of hCG to latent time, number of eggs stripping, increase in egg diameter, increase egg maturity, ovisomatic index value of redfin shark (Epalzeorhynchos frenatum) fish. The treatment used in this research was in injection of hCG with defferent doses is : P0: Control using NaCl 0,9% as much 0,2 ml/kg body weight, P1: Injection of hCG with dose 300 IU/kg body weight, P2: Injection of hCG with dose 500 IU/kg body weight, P3: Injection of hCG with dose 700 IU/kg body weight. The result showed that hCG dose of 500 IU/kg of body weight was the best in turn of latent time obtained 7 hours 54 minutes, number of eggs resulted 323stripping, increase in egg diameter 0,09 mm, increase egg maturity 18% and ovisomatic index value 14%.Keyword: hCG, Ovulation, Eggs Quality,E. frenatum